Intersecting health burdens: oral health, non-communicable disease screening, and women's health in rural Tanzania - Gudsoorkar, Priyanka; Dudhbhate, Anay; Klabak, Jessica; Klabak, Steve; Nolan, Rachael (Frontiers in Oral Health, 2025)
IntroductionThis cross-sectional study explored the intersection of oral health, other non-communicable diseases (NCDs), and women's health in rural Tanzania, using community-based screenings to identify syndemic patterns of vulnerability and inform integrated care strategies.MethodsA total of 224 adult women were recruited during outreach events in three Rorya District villages of Burere, Nyambogo, and Roche in July 2023. Clinical oral examinations were conducted alongside biomarker analysis using the PerioMonitor™, as well as survey-based assessments, including the Oral Health–Related Quality of Life (OHRQoL) scale and the Hologic Global Women's Health Index (HGWI). A subsample of 45 participants underwent additional screening for blood pressure (BP) and blood glucose levels.ResultsOnly 18.2% of participants reported having received prior BP screening. The mean DMFT score was 5.16, and 40% of the sample showed elevated periodontal inflammation. The average OHRQoL score was 11.15, indicating substantial functional and psychosocial impacts. Among those screened further, 49% were hypertensive, 2% were hyperglycemic, and 18% were hypoglycemic, most without a prior diagnosis.ConclusionsCommunity-based screening proved both feasible and impactful, uncovering overlapping burdens of untreated oral disease, metabolic dysregulation, and unmet preventive care. These findings reflect the structural and clinical dimensions of oral health inequity and align with syndemic theory, underscoring the need for integrated, gender-responsive, and culturally grounded interventions. They also offer a foundation for scalable, sustainable models of care in low-resource settings.